Learning trajectory for teaching 3D shapes using PMRI approach with a mosque construction context - Amelia, Rika; Nurhidayah, Nita; Hanifah, Dinah (CV. Pustaka Literasi Ilmiah, 2024)
The background of this research is based on the importance of students' conceptual understanding of geometry in the context of mosque construction. The geometry of the space has an important role in creating a beautiful and meaningful mosque design. The aim of this research is to understand the extent to which the PMRI approach can be applied to spatial geometry in the context of mosque construction. This research uses a design research method with a PMRI (Indonesian Realistic Mathematics Education) approach for class VIII students at Ulul Albab Takokak Cianjur Integrated Qur'an Middle School with a focus on Geometry and Space Building material. Data collection was carried out by means of observation, interviews and documentation. The results of this research are that students can find out how the concept of building space can be applied to everyday life, especially in building mosques.